Supplementation of fungal and/or bacterial phytase in broiler diets formulated with reduced phosphorus level and different calcium contents - Nardelli,Nicole Batelli de Souza (2018)
ABSTRACT The objective of the current study was to evaluate the effects of three calcium:available phosphorus (Ca:aP) ratios and different supplementation with phytases from different origins on performance and ash, Ca, and P contents in the tibia of broilers. A total of 900 male broilers (22 to 35 days old) were fed ten dietary treatments in a completely randomized design. A 3 × 3 + 1 factorial scheme was used, corresponding to three Ca:aP ratios (4.5:1.0, 6.0:1.0, and 7.5:1.0) and three different supplementations with phytases from different origins (isolated or combined supplementation with bacterial and fungal phytase), plus a control diet. Regardless of the dietary Ca:aP ratio, the isolated use of bacterial phytase provided better feed conversion than the fungal phytase but did not differ from combined supplementation with bacterial and fungal phytase. However, regardless of the supplemented phytase, the 7.5:1.0 Ca:aP ratio decreased the feed conversion. Best results for bone P deposition were observed using diets containing the 4.5:1.0 Ca:aP and fungal phytase or the 4.5:1 and 6.0:1 Ca:aP ratios using the bacterial phytase. In general, when the parameters of feed conversion, bone ash, and P content in tibia are considered together, diets containing a 4.5:1.0 or 6.0:1.0 Ca:aP ratio and 1,500 FTU kg−1 bacterial phytase, or a 4.5:1.0 Ca:aP ratio using fungal phytase and only 1.0 g kg−1 available phosphorus provide better results.